The kaleidoscope of the glass ceiling: experiences of Pakistani female doctors – a qualitative narrative inquiry - Nadeem, Amina; Yasmeen, Rahila (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the extent and factors leading to the glass ceiling for Pakistani female doctors in leadership positions. Method: The qualitative narrative study was conducted the Department of Medical Education, Riphah International University, Islamabad, Pakistan from March to July 2021, and comprised female doctors with 10-15 years of professional experience who were either currently at top leadership position or had retired from such a position in public and private medical clinical setups and medical colleges. Data was collected using in-depth interviews conducted through Zoom due to the coronavirus disease-2019 pandemic. The transcribed data was processed using ATLAS.ti.9 software for thematic analysis with an inductive approach. Results: Of the 9 subjects aged 47-72 years having professional experience of 11-39 years, 4(44.4%) were clinicians, 3(33.3%) had basic medical science background and 2(22.2%) were health profession educationists. In terms of qualifications, 4(44.4%) were PhDs, 4(44.4%) were Fellows of the College of Physicians and Surgeons, Pakistan, and 1(11.1%) had an M. Phil. Besides, 4(44.4%) subjects were from the public sector, and 5(55.5%) from the private sector, 1(11.1%) had retired from service. The extent of experiencing the glass ceiling was common to all but 1(11.1%) participant. Factors identified included ‘institutional challenges’, ‘family support issues’, ‘personal challenges’ and ‘societal unacceptance’. Detailed analysis revealed that women in leadership positions faced ‘malintent of seniors’, ‘discrimination’, ‘stereotyping’, ‘lack of mentors’ and ‘ethnic background conditioning’ at the institutional level. On the personal front, they faced ‘lack of support of in-laws’, ‘insecurity of husbands’, ‘need of personal attributes’ and ‘beauty as a barrier’. Conclusion: The glass ceiling was found to be a challenge faced by Pakistani female doctors in leadership positions in both clinical settings and academia. Key Words: Glass ceiling, Leadership positions, Health profession.